Development Of Islamic Career Guidance Media Through Website-Based Information Services To Improve Career Understanding Of Grade Xii Students At Smk Assalaam Bandung - Bayu Permana; Isep Zainal Arifin; Asep Iwan Setiawan (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2025)
This study aims to develop an integrative and Islamic website-based career selection information service media to improve career understanding of grade XII students at SMK Assalaam Bandung. The background of this study is based on various problems in the field, such as low student career understanding, the dominant choice of working after graduation without considering potential development through higher education, the inconsistency between the results of aptitude tests and parental expectations, and the limited guidance and counseling services that are only provided in grade XII. This study uses a Research and Development (R&D) approach with qualitative methods. The media development procedure is carried out through the following stages: identification of potential and problems, data collection, product design, validation, revision, trials, until producing the final product in the form of an Islamic career website. The results of the study indicate that this media is considered suitable by students for use in guidance and counseling services, because it is able to provide extensive, interesting, and easily accessible information related to career understanding that is in accordance with Islamic values.